2010
DOI: 10.21236/ada544674
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Energetic Materials by Rapid Expansion of a Supercritical Solution into Aqueous Solution (RESS-AS) Process

Abstract: Energetic crystalline nanoparticles have many benefits when incorporated into a propellant or explosive. They have been shown to be less sensitive to impact and can also change the energetic performance of a propellant or explosive. In this study, two processes are investigated and compared for producing nano-scale energetic oxidizer particles. Rapid Expansion of a Supercritical Solution (RESS) was investigated and a similar process called the Rapid Expansion of a Supercritical Solution into an Aqueous Solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…After the success of the RESS process, Essel et al developed a new method based on that technique called RESS-AS, which as first reported in 2010 [ 71 ]. RESS-AS uses the versatility of the RESS process, while spraying into an aqueous solution containing a dispersant and/or growth inhibitor [ 72 ]. They reported [ 73 ] the synthesis of 30 nm RDX in a pH 7-stabilized solution.…”
Section: Reviewmentioning
confidence: 99%
“…After the success of the RESS process, Essel et al developed a new method based on that technique called RESS-AS, which as first reported in 2010 [ 71 ]. RESS-AS uses the versatility of the RESS process, while spraying into an aqueous solution containing a dispersant and/or growth inhibitor [ 72 ]. They reported [ 73 ] the synthesis of 30 nm RDX in a pH 7-stabilized solution.…”
Section: Reviewmentioning
confidence: 99%
“…Some authors report the use of milling [7,8] though the risk of unintentional decomposition initiation due to high energy transfer to the energetic compounds remains high. Contrary, bottom-up spray processes like electrospray [9], rapid expansion of supercritical solutions (RESS) [10,11] or spray flash evaporation (SFE) yield better control of heat transfer and reduce thus the risk of unintentional decomposition.…”
Section: Introductionmentioning
confidence: 99%